THE LONGING FOR THE BELOVED: MYSTICAL JOURNEY BEHIND THE HOMECOMING TRADITION ON EID AL-FITR IN INDONESIA AND SONGKRAN INTHAILAND - Sri Hariyatmi (International Journal of Humanity Studies (IJHS), 2019)
On the day of Eid al-Fitr and Songkran celebration, massive exodus from big cities such as Jakarta and Bangkok to rural areas in Indonesia and Thailand takes place as people wish to celebrate the tradition with the loved ones at home. Hence, this mass departure turns the capital into a temporary desolate city. This paper aimed at unveiling the symbolic meaning behind the largest annual homecoming of family reunion in Indonesia and Thailand to observe Eid al-Fitr and Songkran feast. This qualitative research examined the symbolisms in these two most-celebrated festivals in Indonesia and Thailand calendar that breathe similarity with Sufi (Islamic mysticism) imagery. By applying hermeneutic approach specifically of Paul Ricouer as theoretical concept, the finding shows that the main symbolism in Eid al-Fitr and Songkran, the homecoming, demonstrates the core symbolism in Sufi tradition. This symbol is a metaphor of union or invitation for union with the beloved as the ultimate point in Sufi tradition.